Carta de Roberto H. Todd a Charles D. Hilles - Todd, Roberto H.; Hilles, Charles D. (My University, 1912)
Carta relacionada al envío de una carta al Presidente.
Keywords: Hilles, Charles D.--Correspondence.; Hilles, Charles D.--Correspondencia.; Todd, Roberto H.--Correspondencia.; Todd, Roberto H.--Correspondence.; Puerto Rico--Politics and government.; Puerto Rico--Política y gobierno.